Molecular characterization and expression of H5, N1 and NS1 recombinant proteins of avian influenza virus subtype H5N1 in Pichia pastoris - Abubakar, Mustapha Bala (2011)
Avian influenza (AI) subtype H5N1 is one of the major threats to the poultry industry with significant human health implication worldwide. It still remains the most feared poultry disease in recent times. In the last 46 years, over 26 outbreaks of H5N1 had been documented worldwide. This rapidly evolving pathogen of both veterinary and human health first emerged in 1996 from apparently healthy ducks in Southern China. It spread to over 60 countries in Eurasia, over 500 million poultry were culled, 505 human cases were recorded with over 300 mortality. It is a highly contagious viral disease in poultry with 100% morbidity and mortality in susceptible birds. This disease known as highly pathogenic avian influenza (HPAI), is listed as a notifiable disease by the Office International Des Epizootes (OIE) under List A disease. All HPAI viruses were considered to be of H5 or H7 haemagglutinin subtype.In order to isolate, amplify, clone and express H5, N1 and NS gene of AIV virus subtype H5NI, Pichia pastoris expression system was used. They were successfully cloned and expressed in the methylotrophic yeast Pichia pastoris. The haemagglutinin (H5HA) and nonstructural protein (NS1NS) recombinant proteins were generated using sticky ends ligation insertion of these genes into the multiple cloning sites of pPICZA and pPICZαA expression vectors, respectively. The inserted genes were confirmed by restriction enzymes analysis, polymerase chain reaction (PCR) and deoxyribonucleic acid DNA sequencing analysis. The recombinant plasmid construct were appropriately linearized and integrated into the chromosomal genome locus of Pichia pastoris by transformation through single cross over phenomena by electroporation. Transformation efficiency were observed to be enhanced significantly (P<0.05) with more than 100 folds after pretreatment of Pichia pastoris competent cells with 0.1M Lithium acetate (LiAc) and 10mM Dithiothreitol (DTT). Other factors involved include concentration of linearized plasmid DNA, cell biomass density, cell growth phase and restriction enzymes used for the digestion of the plasmid. All these put together, significantly (P<0.05) enhances the transformation efficiency by electroporation using 1.5 Kv, 2.5 μF and 200 Ώ with over a 100 fold difference with a minimum of 2.5 x 105 transformants/μg of DNA. The recombinant H5 and NS1 proteins were expressed in methylotrophic yeast Pichia pastoris using shake flask high cell density fermentation as intracellular protein via pPICZA and as secretory protein via pPICZαA respectively. An optimum condition of 2.0% periodic methanol induction of 120 hrs and 216 hrs post induction time using complex media composition (YPTG/YPTM). An appropriate depression/repression switching of glycerol to methanol enriched complex media for the H5 and NS1 respectively, under the temperature of 250C at 250 rpm for ten successive days with 80% aeration at a pH 8.0 were observed to be optimal expression conditions. The in vitro expressions of the fusion protein were confirmed by the sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE) and Western blot analysis. These analysis detected a molecular weight of full-length H5HA and NS1NS approximately ~ 88kDa and ~ 28kDa, respectively. There was a clear difference between the first 72 hrs and the subsequent hours post induction in H5HA expression dynamics while in respect of NS1NS the expression was evident at the 8th day post induction until the 10th day. In addition there was significant increase (P<0.05) in the growth of cell biomass density at repression/depression stage when simple minimum media and complex media were compared. The study also revealed that the expressed recombinant protein was considered suitable as a potential diagnostic antigen for serological assay. In an in vitro diagnostic assay the recombinant protein expressed was applied as a coating antigen in an in-house developed preliminary ELISA assay for detection of avian influenza subtype H5N1, NS1 specific antibody. The results of the experiment showed that the known standard positive polyclonal sera (Abcam®, USA) reacted specifically with the purified recombinant NS1 protein as a coating antigen, thus, further confirming that the recombinant protein has properly folded and its antigenicity is maintained. Besides, it was also shown that the recombinant protein and the antibody are specific and homologous. When positive cell lysate and negative cell lysate based ELISA results were compared, more than three-fold difference was observed, which further reaffirmed the specificity and homologous nature of the recombinant protein. In addition preliminary ELISA assay based on the commercial antibody against the recombinant protein has showed a good correlation with an R2 value= 0.972. In summary, the current study has produced a recombinant H5 and NS1 recombinant protein in an in vitro, expression using single cell eukaryotic Pichia pastoris expression. This recombinant protein has demonstrated potential diagnostic values for avian influenza virus subtype H5N1: NS1 detection and identification. Recombinant plasmid transformation method has been remarkably enhanced via thiol compound pretreatment prior to electroporation. These new recombinant DNA technology could offer a niche for more efficient, safe, cheap and easy ways of generating in vitro diagnostic antigen as against the old traditional and cumbersome method of using whole viral particles antigens. Further investigation, understanding and application of this DNA technology could open up another niche into diagnostics and subunit vectored vaccine using Pichia pastoris in an effort to control the scourge of rapidly evolving epidemic of avian influenza.